Twist1 induces chromosomal instability (CIN) in colorectal cancer cells. (27th April 2020) - Khot, Maithilee; Sreekumar, Dyuthi; Jahagirdar, Sanika; Kulkarni, Apoorva; Hari, Kishore; Faseela, Elangoli Ebrahimkutty; Sabarinathan, Radhakrishnan; Jolly, Mohit Kumar; Sengupta, Kundan
Abstract: Twist1 is a basic helix-loop-helix transcription factor, essential during early development in mammals. While Twist1 induces epithelial-to-mesenchymal transition (EMT), here we show that Twist1 overexpression enhances nuclear and mitotic aberrations. This is accompanied by an increase in whole chromosomal copy number gains and losses, underscoring the role of Twist1 in inducing chromosomal instability (CIN) in colorectal cancer cells. Array comparative genomic hybridization (array CGH) analysis further shows sub-chromosomal deletions, consistent with an increased frequency of DNA double strand breaks (DSBs). Remarkably, Twist1 overexpression downmodulates key cell cycle checkpoint factors—Bub1, BubR1, Mad1 and Mad2—that regulate CIN. Mathematical simulations using the RACIPE tool show a negative correlation of Twist1 with E-cadherin and BubR1. Data analyses of gene expression profiles of patient samples from The Cancer Genome Atlas (TCGA) reveal a positive correlation between Twist1 and mesenchymal genes across cancers, whereas the correlation of TWIST1 with CIN and DSB genes is cancer subtype-specific. Taken together, these studies highlight the mechanistic involvement of Twist1 in the deregulation of factors that maintain genome stability during EMT in colorectal cancer cells. Twist1 overexpression enhances genome instability in the context of EMT that further contributes to cellular heterogeneity. In addition, these studies imply that Twist1 downmodulates nuclear lamins that further alter spatiotemporal organization of the cancer genome and epigenome. Notwithstanding their genetic background, colorectal cancer cells nevertheless maintain their overall ploidy, while the downstream effects of Twist1 enhance CIN and DNA damage enriching for sub-populations of aggressive cancer cells.